Non-invasive Ultra-early in Utero Detection and Precision CRISPR-mediated Correction of Monogenic Embryonic Mutations: A Critical Appraisal of a Hypothetical Therapeutic Framework - Stefan Bittmann; Elisabeth Luchter; Elena Moschüring-Alieva (Asian Journal of Medicine and Health, 2026)
Advances in circulating placental DNA analysis and in programmable genome editing have developed largely in parallel, yet their conjunction has generated an increasingly discussed proposition: that a pathogenic single-gene variant might be identified non-invasively at the earliest stage of pregnancy and corrected in situ before irreversible pathology develops. This review examines whether that proposition is presently coherent as a therapeutic framework, rather than merely attractive as an idea. The analysis synthesises evidence on the provenance and kinetics of cell-free placental DNA, the analytical performance of relative mutation dosage, relative haplotype dosage, targeted haplotyping and cell-based prenatal diagnosis, and the preclinical record of nuclease-dependent editing, base editing and prime editing delivered to the fetal compartment by viral and lipid-nanoparticle carriers. Evidence quality was appraised with attention to study design, model relevance, endpoint validity, replication and the distance between mechanistic demonstration and clinical benefit. Three findings dominate. First, the detection half of the framework is constrained less by sequencing chemistry than by biology: circulating fetal-derived DNA is placental in origin, is present at low fractional abundance in the earliest weeks, and is an imperfect proxy for the fetal genotype. Second, the therapeutic half rests almost entirely on rodent studies in which editing efficiencies, delivery routes and endpoints do not correspond to the requirements of a human first-trimester intervention, and the only in utero therapies tested in human pregnancies have been protein and cell based rather than gene editing. Third, the interval implied by ultra-early diagnosis is precisely the interval in which delivery, dosing and germ-cell exposure are least characterised. The framework is therefore best regarded as a research programme with identifiable and testable intermediate objectives, not as an imminent clinical pathway. Priorities include gestational-age-resolved fetal fraction studies, editing outcome measurement at single-cell resolution, large-animal dosimetry, and governance work addressing the somatic and germline boundary in prenatal intervention.